Functional Nanomaterials for Optoelectronics and Photocatalysis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is a thematic collection works examining nanomaterials that display functionalities in optoelectronics, photocatalysis and photovoltaics. It includes research works on oxide, metallic and hybrid nanomaterials. Herein, topics range from light-emitting diodes, new materials and photocatalysis for dye degradation and energy production.